ACADEMIC WRITING TEXTBOOK - Abla BENBELLAL (BLIDA 2- FACULTY OF ARTS AND LANGUAGES, 2026)
The primary objective of this course is to help Master’s students develop the skills necessary for successful dissertation writing.
Keywords: ACADEMIC WRITING; TEXTBOOK